Characteristic Analysis of Digital Large Flow Emulsion Relief Valve. (27th May 2020) - Zeng, Qing-liang; Tian, Ming-qian; Wan, Li-rong; Dai, Han-zheng; Yang, Yang; Sun, Zhi-yuan; Lu, Yan-jie; Liu, Fang-quan
Abstract : The relief valve is an important control and overload protection component of the emulsion pumping station. Its performance will affect the overall performance of the emulsion pumping station and the stable and intelligent control of the working surface. However, the research on high pressure and large flow relief valve for mine emulsion pumping station is still inadequate. In order to meet the requirements of emulsion pump station for large flow sensitivity, stability, reliability, and remote intelligent control of overflow valve, this paper uses the digital control method to establish the mathematical model of the relief valve and uses the software such as AMESim to its dynamic characteristics. The simulation results show that the structural parameters such as spool quality, damping hole, and spring stiffness have an effect on the working characteristics of the relief valve. It also provides reference for the intelligent control research of the large flow relief valve for the emulsion pumping station.